Canva-Based Learning Media Creation Training for Elementary School Teachers - Pasa*, Inda Tri; Nur, Fauziah; Wardani, Ivana; Sukarwoto, Sukarwoto; Cahyadi, Catra Indra; Sylvia, Tiara; Hutabarat, Liber Tommy; Diriyanti, Susi; Akbar, Muhammad Caesar; Matthew, Jason Juan (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Community service activities aim to provide participants with experience using Canva to create more interactive learning media and increase participants' motivation in teaching. Canva is currently the most popular website application for graphic design and brand building. Participants can also use Canva as a learning medium; they can also use Canva for social media and to support school activities. Participants can take advantage of better and more templates with Canva Pro. This training was attended by 17 participants: school principals, teachers, and administrative participants. The methods include lectures, question-and-answer discussions, demonstrations, and group presentations. The evaluation showed participants could make PowerPoint presentations, flyers, and class schedules. In the results of the questionnaire recapitulation from 17 participants, the maximum score was 100, obtained from respondents with an average score of 92, with the highest participant score being 100 and a minimum score of 83. Apart from teachers, students can also use the Canva application.